2020
DOI: 10.1177/2047173420927665
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of personal financial literacy teaching and learning in Ontario high schools

Abstract: The purpose of the study was to examine the experiences of current high school students and teachers in Ontario regarding their experiences with personal financial curriculum and teaching at the secondary level, and to identify the ways in which this important educational experience may have helped prepare students to become financially literate. We considered this overarching issue using a transdisciplinary lens from the perspective of the three stakeholder groups. Using a case study research design, the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Still, they admitted to having difficulty in conveying information. Teachers perceive they lack teaching experience and need to prepare for better financial literacy and teaching so that students gain more meaningful and valuable educational experiences (Ferrer, 2018;Henning & Lucey, 2017;Imelda et al, 2017;Matheson et al, 2020). The above finding is consistent with the study by Tanase and Lucey (2017) examined that the majority of preservice teachers have a narrow or moderate concept of the relationship between mathematics and financial literacy.…”
Section: Problem Statementmentioning
confidence: 54%
“…Still, they admitted to having difficulty in conveying information. Teachers perceive they lack teaching experience and need to prepare for better financial literacy and teaching so that students gain more meaningful and valuable educational experiences (Ferrer, 2018;Henning & Lucey, 2017;Imelda et al, 2017;Matheson et al, 2020). The above finding is consistent with the study by Tanase and Lucey (2017) examined that the majority of preservice teachers have a narrow or moderate concept of the relationship between mathematics and financial literacy.…”
Section: Problem Statementmentioning
confidence: 54%
“…The document targeted the development of financial literacy knowledge and skills with a focus on decision-making, critical thinking, problem-solving and critical literacy. Of particular interest was the This article reports on the findings of the study carried out by Matheson (2019) regarding the perspectives of students on their experiences with transdisciplinary teaching and learning of personal financial literacy in school. The study surveyed 344 participants drawn from one Ontario college and one Ontario university.…”
Section: Methodsmentioning
confidence: 99%
“…However, student assessments of financial literacy curricula would serve to inform and enlighten their learning experience, resulting in increased value and meaning for their paths ahead. This article reports the findings of a financial literacy study (Matheson, 2019) that examined the perspectives of students on their experiences with teaching and learning of personal financial literacy in school. The study identifies student-centered inquiry and implementation challenges as educators seek to equip students with the skills and knowledge they are expected to need going forward.…”
Section: Perspectives Des éTudiants Sur L'éducation Financière Transd...mentioning
confidence: 99%
“…Amagir et al, 2018;Harter and Harter, 2009;Walstad et al, 2010) have shown that specific programs have positive effects on student knowledge of personal finance concepts, others (e.g. Mandell, 2008;Matheson et al, 2020;Peng et al, 2007) have found little to no support for the conclusion that financial education improves student knowledge or prepares students to be financially literate. Walstad et al (2017) evaluated financial education for a variety of groups and issues and found financial education to have positive outcomes but that the outcomes vary for different groups.…”
Section: Prior Researchmentioning
confidence: 99%